Development of 6-inch h-BN thick wafers - Z. Alemoush; M. Almohammad; J. Li; J. Y. Lin; H. X. Jiang (AIP Advances)
We report the first successful synthesis of 40 μm thick h-BN wafers with a diameter of 6 in. using hydride vapor phase epitaxy. This accomplishment was made possible by employing BCl3 as the B precursor to eliminate carbon impurities, utilizing inert N2 as the carrier and separation gas to isolate BCl3 and NH3 gas sources, and implementing low-pressure growth to prevent parasitic reactions in the gas phase. These strategies enabled the growth of h-BN wafers 6 in. in diameter with improved uniformity in thickness and crystallinity. Analysis through x-ray diffraction, selected area electron diffraction, and transmission electron microscopy revealed that the wafer deposited at the lowest pressure of 20 Torr exhibited highest crystalline quality with measured c-lattice constant c = 6.66 Å and an a-lattice constant a = 2.48 Å, in good agreement with the expected lattice parameters of phase-pure h-BN. Time-resolved photoluminescence emission spectroscopy unveiled a dominant emission line near 3.41 eV, with a recombination lifetime of 2.7 ns at room temperature. These spectroscopic characteristics, when considered alongside a previous theoretical study, suggest that nitrogen vacancies (VN) constitute the primary defects in these large-diameter h-BN wafers. The achievement of 6 in. diameter wafers with substantial thickness represents a significant advancement in h-BN development, paving the way for the industrial adoption of h-BN technologies, with implications for quantum information and technology, single photon emitters, neutron detectors, power electronics, and deep UV photonics.